Unmasking a Case of Asymptomatic Charcot-Marie-Tooth Disease (CMT1A) With Vincristine. (16th February 2018) - Jariwal, Roopam; Shoua, Basel; Sabetian, Katayoun; Natarajan, Piruthiviraj; Cobos, Everardo
Charcot-Marie-Tooth (CMT) disease is a hereditary demyelinating disease of the peripheral nervous system that results in sensory and motor dysfunction. CMT includes a spectrum of diseases with different types of mutations in the genes encoding myelin protein, resulting in a variety of dysfunctions in its life cycle. In CMT subtype 1A there is duplication mutation of peripheral myelin protein 22 gene on chromosome 17. Incomplete penetrance, gene-dosage effect, and variable expressivity can attribute to the asymptomatic nature of the disease in some subset of patients. Vincristine administration is contraindicated in patients who are alrea\dy diagnosed with CMT disease. We report a case of asymptomatic CMT disease unmasked only by the neurotoxic effects of vincristine. Genetic testing for a patient with a preexisting family background of inherited diseases before starting vincristine therapy can potentially prevent a disability.